Control System Semi-Automatic Palembang Songket Shawl Using Splay Tree Algorithm Based ATMega 8 - sholihin lihin hin (IAES Indonesia Section, 2015)
Songket shawl is handcrafted hereditary in South Sumatra, but is also a manufacture shawls for songket which is also typical of Palembang. Songket shawls device consists of makers crutch, stick motif maker, dividers, and bobbin. Furthermore, researchers will apply a calculation using the splay tree algorithm to identify, to detected and stop the process of command at the time of semi-otomamatis will be work, researchers will also discuss well with experts. Semi-automation weaving machines are expected to contribute the craftsmen to improve results weaving it’s , such as looms and supplies sensors and application programs that can be used and then will make the craft of weaving typical areas of South Sumatra. This research is expected to produce a patent for songket and scarf with a semi-automatic machine patents and developed with several motifs. This research will measure are performance of semi-automatic by showing results of measurement of the strength or speed DC motor to throw and pull the threads, be it gold thread and yarn. Limar, regulated Pulse Width Mudulation (PWM) so that the performance of motor speed can be adjusted, from measurement results are known in the hurling thread from a distance of 0 - 30 cm. When a thread already determined the maximum distance that the duty cycle of the PWM value of 0 cm distance position obtained 0 % duty cylce and from a distance of 30 cm till maximum gained 3.12% duty cycle. Furthermore, measuring the value of the AT Mega 8 is connected to the amplifier IC L293D DC motor with which the process of making a semi automatic loom requires a 12 MHz crystal so that the cycle speed to 12 MHz/12 = 1 MHz, which means time is 1 microsecond pulse period. Loom’s will be connected to a computer for programming process as data base in terms of the AT Mega 8 language in use, so that the output of the weaving songket shawl can be arranged with advance determined motives that would be desirable is useful to prevent or protect hurling thread - the thread excessive, so that motifs are in use should be appropriate.